Une place pour les migrants ? - Greiner, Dominique ca. 20./21. Jh. (Revue d'éthique et de théologie morale, 2025)
Building on the exchanges that took place during the study day, this contribution sets out some convictions on the conditions for a realistic ethical discourse on migration, a subject that is rarely discussed in a calm manner in the public arena. It then looks at what our way of dealing with administrative requests from migrants and refugees reveals about the way we function as a society. Finally, it resituates the question of the integration of migrants within the wider context of the social integration of the poor.